Literature Review: Antioxidant Activity of Water Apple Leaves (Syzygium aqueum) - Justisia, Adilla; Susianti; Jausal, Anisa Nuraisa; Busman, Hendri (Medula, 2025)
Antioxidant is a complex inhibit, prevent or dampen the reactions of free radicals and oxidants, as well as to prevent tissue damage. Antioxidant works by donating one of its electron to oxidant compounds thereby inhibiting the activity of these oxidant compounds. An imbalance between antioxidants and free radicals, where free radicals are more prevalent, can damage molecular organisms and cause oxidative stress that triggers damage to body cells. Oxidative damage to DNA triggers mutations that initiates cancer, cardiovascular disease, neurodegenerative disorder, autoimmune diseases, aging processes and several hereditary diseases. Currently, the use of natural antioxidants as traditional treatments is widely consumed by the community. Natural antioxidants are found in several plant sources, it is known to be more affordable and have lower side effects, making it as popular treatment choice in the community. One of the plants with a high antioxidant content is the water apple leaf (Syzygium aqueum) which rich in flavonoids, phenolics, and tannins. DPPH (2,2-diphenyl-1-picrylhydrazyl) is a common method to measure antioxidant activity, it works with the principle of hydrogen capture from antioxidants by free radicals. The parameter IC50 is used to represents the sample concentration required to capture 50% of DPPH radicals. Several studies using the DPPH method have shown that water apple leaves have strong antioxidant activity, indicated by its low IC50 value. The lower the IC50 value, the stronger the antioxidant activity.